Conducting Polymer Coating on a High-Voltage Cathode Based on Soft Chemistry Approach toward Improving Battery Performance - Kwon, Yonguk; Lee, Yongho; Kim, Sang-Ok; Kim, Hyung-Seok; Kim, Ki Jae; Byun, Dongjin; Choi, Wonchang (American Chemical Society, 2018)
The surface of a 5 V class LiNi0.5Mn1.5O4 particle is modified with poly(3,4-ethylenedioxythiophene) (PEDOT) conducting polymer by utilizing the hydrophobic characteristics of the 3,4-ethylenedioxythiophene (EDOT) monomer and the tail group of cetyl trimethyl ammonium bromide (CTAB) surfactants, in addition to the electrostatic attraction between cationic CTAB surfactant and cathode materials with a negative potential in aqueous solution. With this novel concept, we design and prepare a uniform EDOT monomer layer on the cathode materials, and chemical polymerization of the EDOT coating layer is then carried out to achieve PEDOT-coated cathode materials via a simple one-pot preparation process. This uniform conducting polymer layer provides notable improvement in the power characteristics of electrodes, and stable electrochemical performance can be obtained especially at severe operating conditions such as the fully charged state and elevated temperatures owing to the successful suppression of the side reaction between the oxide particle and the electrolyte as well as the suppression of Mn dissolution from the oxide material.